ANALISIS USAHATANI UBI KAYU (Manihot utilissima) - Muhammad Thamrin; Ainul Mardhiyah; Samsul Efendi Marpaung (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This research was conducted to know the effect of production factors (land, seeds, labor, and fertilizers) on the cassava farming income, to know the feasibility of the cassava farming. Census method is used on this research, took all the population of the sample through the method of Cobb-Douglas analysis of, Descriptive and R / C ratio. The results of the research of land variable, seeds, labor and fertilizers significant effect and simultaneously (synchronously) to the income of the cassava farmers. In partial significant effect of land variable. Meanwhile the variable of seeds, labor and fertilizers had no significant effect on the the cassava farming income. Based on the analysis of the R / C ratio with a value of 7.5> 1, the cassava farming in the area of research deserves to be developed.Keywords : analysis, income, farming